Randomized Clinical Trial on Epidural Versus Patient-controlled Analgesia for Laparoscopic Colorectal Surgery Within an Enhanced Recovery Pathway. Issue 4 (April 2015) - Hübner, Martin; Blanc, Catherine; Roulin, Didier; Winiker, Michael; Gander, Sylvain; Demartines, Nicolas
<x xml:space="preserve">Abstract</x> Objective: To compare epidural analgesia (EDA) to patient-controlled opioid-based analgesia (PCA) in patients undergoing laparoscopic colorectal surgery. Background: EDA is mainstay of multimodal pain management within enhanced recovery pathways [enhanced recovery after surgery (ERAS)]. For laparoscopic colorectal resections, the benefit of epidurals remains debated. Some consider EDA as useful, whereas others perceive epidurals as unnecessary or even deleterious. Methods: A total of 128 patients undergoing elective laparoscopic colorectal resections were enrolled in a randomized clinical trial comparing EDA versus PCA. Primary end point was medical recovery. Overall complications, hospital stay, perioperative vasopressor requirements, and postoperative pain scores were secondary outcome measures. Analysis was performed according to the intention-to-treat principle. Results: Final analysis included 65 EDA patients and 57 PCA patients. Both groups were similar regarding baseline characteristics. Medical recovery required a median of 5 days (interquartile range [IQR], 3–7.5 days) in EDA patients and 4 days (IQR, 3–6 days) in the PCA group (P = 0.082). PCA patients had significantly less overall complications [19 (33%) vs 35 (54%); P = 0.029] but a similar hospital stay [5 days (IQR, 4–8 days) vs 7 days (IQR, 4.5–12 days); P = 0.434]. Significantly more EDA patients needed vasopressor treatment perioperatively (90% vs 74%, P = 0.018), the day of surgery (27% vs 4%, P < 0.001), and on postoperative day 1 (29% vs 4%, P < 0.001), whereas no difference in postoperative pain scores was noted. Conclusions: Epidurals seem to slow down recovery after laparoscopic colorectal resections without adding obvious benefits. EDA can therefore not be recommended as part of ERAS pathways in laparoscopic colorectal surgery.